Paradigma Baru Pendidikan Anak Usia Dini Berdasarkan Karya Munif Chatib “Orangtuanya Manusia” (THUFULA, 2019)
The researchers 'interest in discussing the book by Munif Chatib's "Parents of Man" was motivated by researchers' concerns in following the development of the AUD and observing parenting in the community. The purpose of this study was to explain Munif Chatib's ideas in reconstructing a new paradigm of AUD education at home and school. This research was a library research. The results showed that there were seven (7) new paradigms in AUD parenting according to Munif Chatib, namely: (1) providing the right stimulus to boost AUD intelligence; (2) the success of AUD education, (3) generating AUD self-confidence; (4) identifying AUD talents and interests; (5) Choosing the right school; (6) help children learn at home; and (7) overcoming the influence of media and pornography.